Woman in the role of the mother. Propositions of Anastazja Dzieduszycka née Jełowicka (1842–1890) - Falkowska, Joanna (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The main objective of the paper is to show the views of Anastazja Dzieduszycka née Jełowiecka on the role of the mother. This teacher, activist and pedagogical columnist was convinced of the great importance of this task as well as the responsibilities that lie with women as aresult. A mother should be the first teacher for her child, instil Christian values in it, prepare it to measure up to the responsibilities it will have towards society and especially to diligent work. The author was also of the opinion that a woman–mother of her time should be a conscious person. She should keep up with the times and adapt her actions to the changing reality. She held the family’s happiness, well-being, and morality, for which the woman is largely responsible, in high regard. It is she who is able, with her work and involvement, using the appropriate means, to make family life reflect Christian values.
Keywords: mother; upbringing; work; Anastazja Dzieduszycka née Jełowicka